Concepções de ensino de linguagem dos alunos egressos do Curso de Letras da Universidade Estadual de Ponta Grossa - Nogueira, Rosemeri Teresinha Hoffmann (2006)
This research aims to evidence the importance of the language conceptions to be taken as the beginning in the definition of teaching/learning methodologies of the Portuguese language and to have the teacher to be aware that his pedagogic practice in the Portuguese teaching has direct relation with his language conception. This research aimed to investigate which language teaching conception that is according to the pedagogic practice of the deviated student and the Portuguese language teacher former of the language course of the State University of Ponta Grossa. Through this research, it was checked how the deviated students evaluate the language course and the questions releated to the theories and practices that give support to the initial formation of the teacher. The research is devided into five chapters structured this way: the first one regards the theories related to Bakhthin, Geraldi, Suassuna and Travaglia, among others; the second reagards a brief historical of the language course; the third covers the conceptions of the former teachers; the fourth treats the methodological matters; the fifth, the teaching conceptions of the deviated students, the, and the last one focuses the final considerations. This work developed from the methodological paths described by Triviños, that align the procedures with qualitative and quantitative focus, even though, the major enfasis is in the qualitative research, considering that one assists better proposed objectives. This research was classified how the case study, it was used as data gathering a half-structed interwiew with deviated students from the language course with were graduated by the State University of Ponta Grossa in the period of 1993 to 2003 and with teachers from the methodoly and teaching practice subject. The data gathering was performed in 2004 which lasted a year.